2009
DOI: 10.3945/jn.108.100438
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Iodine Concentrations Indicate Iodine Deficiency in Pregnant Thai Women but Iodine Sufficiency in Their School-Aged Children

Abstract: The median urinary iodine concentration (UI) in school-aged children is recommended for assessment of iodine nutrition in populations. If the median UI is adequate in school-aged children, it is usually assumed iodine intakes are also adequate in the remaining population, including pregnant women. But iodine requirements sharply increase during pregnancy. In this study, our aim was to measure UI in pairs of pregnant women and their school-aged children from the same family, who were sharing meals, to directly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
54
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 21 publications
14
54
0
2
Order By: Relevance
“…But one of the studies it has been shown that the median UI in school-aged children could not be used as a surrogate for monitoring the iodine status in pregnancy and that pregnant women should be directly monitored [21].…”
Section: Discussionmentioning
confidence: 99%
“…But one of the studies it has been shown that the median UI in school-aged children could not be used as a surrogate for monitoring the iodine status in pregnancy and that pregnant women should be directly monitored [21].…”
Section: Discussionmentioning
confidence: 99%
“…Namely, during pregnancy, as a result of physiological changes that occur in a woman's body, the amount of excreted urine increases, and therefore it would be more reasonable to compare ioduria in pregnant women in relation to creatinine excretion. Interesting observations were made by Gowachirapant et al [38], who measured ioduria in school-aged children and their mothers being pregnant at the time of the study; these families lived together and had a similar diet. They noted that ioduria in children was correct; while in pregnant women it indicated a deficiency of iodine in the diet.…”
Section: Prace Oryginalnementioning
confidence: 99%
“…A recent review concluded that when the median UIC in SAC or non-pregnant women indicated iodine intake was adequate or above requirements in a region, about half the time pregnant women in that same region had inadequate iodine intake (15) . Multiple studies have reported that when SAC have adequate iodine status (median UIC = 100-199 µg/l), pregnant women are deficient (median UIC < 150 µg/l), and that iodine sufficiency in pregnancy is attained only when the SAC have more-than-adequate (median UIC = 200-299 µg/l) iodine status (14,15,(25)(26)(27)(28) . In an earlier Thai study using similar methodology (25) but in families where not all meals were consumed within the household, despite a median UIC of 200 μg/l in SAC, iodine intakes in pregnant women were inadequate, with a median UIC of only 108 μg/l.…”
Section: Discussionmentioning
confidence: 99%